A EVOLUÇÃO COMUNICATIVA DOS MECANISMOS DE BUSCA: DO TELÉGRAFO À WEB SEMÂNTICA - TOTH, PEDRO HENRIQUE (2017)
In times when the use of the internet and the web are becoming more and more present in the life of the human being, it’s possible to observe the increasing rise of search engines in people's daily life, solving problems such as the simple task of locating a musical sheet or even elaborated scientific articles. Speed, accuracy and simplicity make search engines, today, essential tools in the life of the modern and connected human being, thus creating a dependency of them in the man’s life. The objective of this research is to draw a historical line, addressing the main technologies and scientists involved in the technological development that resulted in the search engines. To do so, this research relies on a solid bibliographic review of books and articles about technology and communication, as well as magazines and reports about the subjects involved. The result of the research culminated in a technological perspective, based on the facts and technologies presented, of an integrated search engine that may become part of the human daily life soon.